Effect of epidural spinal cord stimulation in individuals with sensorimotor complete spinal cord injury: a pilot study - Rybka, Vojtech; Sediva, Kristyna; Spackova, Lenka; Kolar, Pavel; Bradac, Ondrej; Kriz, Jiri (Frontiers in Systems Neuroscience, 2025)
Spinal cord injury (SCI) often results in irreversible sensorimotor and autonomic dysfunction, severely limiting independence and quality of life. Individuals with clinically complete SCI (AIS A) have traditionally been considered beyond functional recovery. This pilot study aimed to evaluate the therapeutic potential and broader impact of epidural spinal cord stimulation (eSCS) on this population. Three participants with chronic, sensorimotor complete thoracic SCI received implantation of a 32-contact epidural stimulator targeting the lumbosacral spinal cord. Personalized stimulation protocols were developed to support lower limb activation and upright posture. Motor, autonomic, and quality of life outcomes were assessed over a 12-month follow-up. All participants achieved independent standing through eSCS-enabled muscle activation, despite the absence of voluntary movement. The intervention led to improvements in postural control and trunk stability, as well as clinically meaningful gains in autonomic functions, including bladder, bowel, and sexual health, alongside reductions in spasticity and neuropathic pain. Importantly, participants reported sustained and substantial improvements in their perceived quality of life. This study provides evidence that eSCS can restore key functional capacities and significantly enhance the quality of life for individuals with sensorimotor complete SCI.